2021
DOI: 10.1249/mss.0000000000002747
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Muscle Metaboreflex Activation after Static Handgrip Exercise

Abstract: PurposeLarger blood pressure (BP) responses to relative-intensity static exercise in men versus women are thought to involve altered muscle metaboreflex activation, but whether this is because of an intrinsic sex difference in metabolite production or differences in muscle strength and absolute load is unknown.MethodsContinuous BP and heart rate were recorded in 200 healthy young men and women (women: n = 109) during 2 min of static handgrip exercise at 30% of maximal voluntary contraction (MVC), followed by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 50 publications
6
25
1
Order By: Relevance
“…We have previously reported a 10-14% increase in HR, 7-20% increase in MAP, and 9-13% increase in MCAv in response to IHG exercise at 30% of MVC until fatigue in postmenopausal women with or without a history of hypertensive pregnancy ( Ranadive et al, 2017 ; Miller et al, 2019 ). Consistent with our previous work and others, we observed similar sustained increases in cardiovascular ( Lewis et al, 1983 ; Sander et al, 2010 ; Ranadive et al, 2017 ; Lee et al, 2021 ) and cerebrovascular variables ( Miller et al, 2019 ) during IHG exercise and post-exercise ischemia. A unique aspect of this study is the inclusion of cerebral hemodynamics (MCAv and CVRi) to assist in interpretation of hemodynamic changes in the cerebral vessels in response to two sympathoexcitatory stressors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We have previously reported a 10-14% increase in HR, 7-20% increase in MAP, and 9-13% increase in MCAv in response to IHG exercise at 30% of MVC until fatigue in postmenopausal women with or without a history of hypertensive pregnancy ( Ranadive et al, 2017 ; Miller et al, 2019 ). Consistent with our previous work and others, we observed similar sustained increases in cardiovascular ( Lewis et al, 1983 ; Sander et al, 2010 ; Ranadive et al, 2017 ; Lee et al, 2021 ) and cerebrovascular variables ( Miller et al, 2019 ) during IHG exercise and post-exercise ischemia. A unique aspect of this study is the inclusion of cerebral hemodynamics (MCAv and CVRi) to assist in interpretation of hemodynamic changes in the cerebral vessels in response to two sympathoexcitatory stressors.…”
Section: Discussionsupporting
confidence: 93%
“…our previous work and others, we observed similar sustained increases in cardiovascular (Lewis et al, 1983;Sander et al, 2010;Ranadive et al, 2017;Lee et al, 2021) and cerebrovascular variables (Miller et al, 2019) during IHG exercise and postexercise ischemia. A unique aspect of this study is the inclusion of cerebral hemodynamics (MCAv and CVRi) to assist in interpretation of hemodynamic changes in the cerebral vessels in response to two sympathoexcitatory stressors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It has been suggested that the absolute (rather than the percentage) ΔMSNA exerts the most influence on target organ responses, and is therefore the most physiologically significant measure (Tanaka et al, 1999). All recent studies (Badrov et al, 2016;Gagnon et al, 2015;Lee et al, 2021;Miller et al, 2019;Notarius et al, 2019;Wenner et al, 2022), with the exception of Keller-Ross et al (2020), that compared MSNA responses to acute physiological stressors (i.e., handgrip exercise and cold pressings) between younger and older individuals reported absolute MSNA changes only. MSNA BF is related to the plasma noradrenaline concentration (Morlin et al, 1983;Ng et al, 1993;Wallin et al, 1987) and renal noradrenaline spillover (Wallin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Keller et al (2022) used fNIRS to assess participants’ cerebral oxygenation during IHE and observed that at a 25% MVC protocol, there was a decrease in oxyhemoglobin in males but an increase in females, which directly affects cognitive performance ( Herold et al, 2019b ; Zhu et al, 2022 ). Additionally, sex differences in matched contraction load contribute to differences in BP responses and cardiac baroreflex sensitivity ( Teixeira et al, 2018 ; Lee et al, 2021 ), which potentially indirectly affects cognitive performance ( Ogoh and Tarumi, 2019 ). Lee et al (2021) reported males having larger acute BP responses during and immediately after the 2-min with 30% MVC exercise than females.…”
Section: Discussionmentioning
confidence: 99%